Dangerous amusements : leisure, the young working class and urban space in britain, c. 1870-1939 - Harrison, Laura (Studies in popular culture (Manchester, England), 2022)
Drawing on an extensive range of sources, from newspapers and institutional records to oral histories and autobiography, this book explores the beginnings of a distinct youth culture in the streets and neighbourhood spaces of late nineteenth and early twentieth century Britain.